Sublimation thermodynamics of nucleobases derived from fast scanning calorimetry. Issue 2 (16th December 2019) - Abdelaziz, A.; Zaitsau, D. H.; Buzyurov, A. V.; Verevkin, S. P.; Schick, C.
Abstract : Fast scanning calorimetry was utilized to measure the sublimation thermodynamics of nucleobases. The results were rationalized at the molecular level. Abstract : The five fundamental units of the genetic code: uracil (U), thymine (T), cytosine (C), adenine (A) and guanine (G) are known for extremely low vapor pressure and low thermal stability at elevated temperatures. Therefore, application of conventional techniques for the determination of sublimation enthalpies and vapor pressures fails to provide accurate results. Recently, a Fast Scanning Calorimetry method (FSC) for vapor pressure determination was developed for investigation of extremely low volatile, as well as for thermally unstable molecular and ionic molecules. This success has encouraged application of the FSC method for determination of vapor pressures and sublimation enthalpies of the five nucleobases, where available literature data are in disarray. The thermodynamic data of the nucleobases available in the literature were collected, evaluated, and combined with our experimental results to reconcile available experimental data. The set of evaluated thermochemical data on the five nucleobases was recommended as the benchmark properties for these thermally labile compounds.